(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This article discusses the theoretical essence of auditing in fruit and vegetable processing enterprises and the mechanisms of its influence on production efficiency. The specific features of the industry - seasonality, perishable raw materials, cold chain, laboratory quality indicators (BRIX, pH, dry matter), the presence of normal and excessive losses - justify the need to organize the audit methodology in a process-centered and risk-based approach. The study interprets the classical principles of auditing in an adapted way to production processes and reveals the role of audit evidence in ensuring the connection between physical flows and financial results. The article scientifically substantiates the importance of audit results in reducing costs, increasing output coefficients, reducing technological variability, and making management decisions based on evidence.